2002
DOI: 10.1093/ajcn/75.4.754
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of supplementation with docosahexaenoic acid–rich tuna oil and its effects on the human milk cytokines interleukin 1β, interleukin 6, and tumor necrosis factor α

Abstract: Consumption of < or = 600 mg DHA and 140 mg EPA/d for 4 wk increased n-3 PUFA concentrations in relevant tissues but did not cause perturbations in cytokine concentrations in human milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 19 publications
3
28
0
Order By: Relevance
“…Our data demonstrate that in lactating women with relatively low fish intake, which is the primary dietary source of DHA, supplementation significantly increased breast milk and circulating DHA in mothers as well as decreased the ratio of n-6:3 in infants. Our results in breast milk are in agreement with several others [13,[35][36][37]39] that used similar doses of DHA during several different time periods of supplementation. Additionally, a recent analysis [40] of a previous dose response study [34] provides an equation relating maternal intake and breast milk DHA output (r 2 ¼0.998), which is in agreement with the current data (r 2 ¼0.995).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data demonstrate that in lactating women with relatively low fish intake, which is the primary dietary source of DHA, supplementation significantly increased breast milk and circulating DHA in mothers as well as decreased the ratio of n-6:3 in infants. Our results in breast milk are in agreement with several others [13,[35][36][37]39] that used similar doses of DHA during several different time periods of supplementation. Additionally, a recent analysis [40] of a previous dose response study [34] provides an equation relating maternal intake and breast milk DHA output (r 2 ¼0.998), which is in agreement with the current data (r 2 ¼0.995).…”
Section: Discussionsupporting
confidence: 93%
“…There was no difference among groups in baseline fish intake as assessed by FFQ or DHA intake over the course of the study determined by 3 day food records, supporting that the increase was due to the supplement. Both doses of supplement increased plasma DHA which is consistent with previous research [35,36] and demonstrated a significant difference between the two doses, which is similar to Hawkes et al [35] that supplemented with 300 and 600 mg of DHA for 4 weeks. Another study with increasing doses only showed a significant difference in plasma with a much higher dose (1021 mg/day DHA as cod liver oil) but demonstrated increase in breast milk DHA at all doses [39].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Breast milk DHA content can be increased by maternal supplementation with fish oil [45] , DHA-rich oil [46,47] or n-3 LCPUFA-rich eggs [47] or by increased maternal fatty fish consumption [48] . Harris et al [45] gave lactating women 5 g/day fish oil for 28 days, 10 g/day fish oil for 14 days or 47 g/day fish oil for 8 days.…”
Section: Increasing the Status Of Dha In Human Breast Milkmentioning
confidence: 99%
“…Levels of DHA in breast milk were 0.1% of total fatty acids at baseline and 0.5, 0.8 and 4.8% of fatty acids after 5, 10 and 47 g/day fish oil, respectively. Hawkes et al [46] gave lactating women placebo, 'low'-dose DHA (300 mg/day) or 'high'-dose DHA (600 mg/day) from day 3 after delivery for 4 weeks. They found that the DHA content of maternal plasma, maternal mononuclear cells, breast milk and breast milk cells increased in relation to DHA intake.…”
Section: Increasing the Status Of Dha In Human Breast Milkmentioning
confidence: 99%